Optimum design of acoustic stealth shape of underwater vehicle model with conning tower - Tang, Yuhang; Wang, Xueren; Miao, Xuhong; Gao, Shengyao; Li, Bing; Peng, Zilong (Frontiers in Physics, 2023)
We present an optimization algorithm for achieving optimal acoustic stealth performance during designing an underwater vehicle shape in the free field using COMSOL-MATLAB integrated software. A component superposition method based on phase interference is adopted to simplify and decompose a nonaxisymmetric complex underwater vehicle model into two main parts: the hull and the conning tower. The shape of underwater vehicle hull is described mathematically with a sequence of undetermined coefficients for optimization. The basic mathematical principle of the proposed method is Kirchhoff approximation, also called planar element method (PEM). Additionally, some examples and experimental results show that this method can realize the automatic optimization design of acoustic stealth shapes for underwater vehicle model in a given frequency band and acoustic incident angle range. The underwater vehicle design has a smooth appearance with low target strength (TS) or angle detection rate for most detection angles and frequency bands after optimized.